Quantum of damages in accident cases / Rohayah Abd. Halim - Abd. Halim, Rohayah (Faculty of Law, 1985)
For this purpose of this Project Paper, an award of damages under Common Law is to be considered as the sum of money payable as compensation for personal injury and fatal injury arising from accident cases. In 19251 Atkin L.J.: "The law as to damages still awaits a scientific statement ...(it is) a branch of the law on which one is less guided by authority laying down definite principles than almost any other matter that one can consider." Damages are compensation in money awarded to the injured party in accident claims. When one person causes harm of any kind to another person whether it is personal injury, damage to property or financial loss the normal remedy which the law gives (if in the circumstances of the case it give right of action at all) is a right to recover, damages. Damages are simply a sum of money given as compensation for loss of harm of any kind. The law on the nature of damages has been stated from time to time in somewhat varying terms by statement judges for example by Discount Denedin in 2 Admiralty Comrs v SS Valeria said: "The true method of expression, I think is that in calculating damages you are to consider what is the pecuniary consideration which will make good to suffer, as far as money can do* so, the loss which he has suffered as the natural result of the wrong done to him."